2019
DOI: 10.1108/el-09-2018-0185
|View full text |Cite
|
Sign up to set email alerts
|

Use and reuse of visual resources in student papers and presentations

Abstract: Purpose The purpose of this study is to explore how undergraduate and graduate students use visual resources in their papers and presentations and what role images play in their academic work. It also focused on analyzing the types of image use/reuse in academic work. Design/methodology/approach This study was designed using an exploratory, qualitative approach. In all, 15 participants were recruited. Multiple sources of data were collected, including visual evidence, questionnaires and interviews. It adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Illustration needs were among users in professional and academic settings, such as students, lecturers, researchers and doctors. Creating presentation slides or preparing study materials were frequently mentioned image use cases (e.g., Beaudoin, 2014; Huang and Kelly, 2013; Matusiak et al , 2019a,b). In medical settings, clinicians use images to support patient diagnoses and colloquia presentations (Beaudoin, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Illustration needs were among users in professional and academic settings, such as students, lecturers, researchers and doctors. Creating presentation slides or preparing study materials were frequently mentioned image use cases (e.g., Beaudoin, 2014; Huang and Kelly, 2013; Matusiak et al , 2019a,b). In medical settings, clinicians use images to support patient diagnoses and colloquia presentations (Beaudoin, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Of the literature reviewed, 20 studies recruited students as participants to investigate everyday image information behavior. Despite this high number, only a handful of studies (Huang & Kelly, 2013;Matusiak, 2013;Matusiak et al, 2019a;Matusiak et al, 2019b) in our dataset intentionally targeted the information needs and seeking behavior of students. The remaining studies examined the daily needs of general image searchers through the eyes of students.…”
Section: Users Targetedmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies offer insight into teaching visual literacy in disciplinary contexts and provide examples of classroom activities (Beaudoin, 2016; Bell, 2014; Matusiak, 2013; Ravas and Stark, 2012). Matusiak et al (2019a, 2019b) examined students’ visual literacy skills and the use of images in the context of academic work in a qualitative exploratory study. The researchers adopted Consensual Qualitative Research (CQR), a method developed in counseling psychology.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…Furthermore, the Assessment Interest Group research team explored the barriers and solutions in assessing the reuse of digital objects outside of digital library systems (O'Gara et al, 2018). Matusiak et al (2019) expanded the notion of use and reuse and found instances of creative and transformative reuse in the academic context. These studies identify categories of reuse that can be applied in further evaluation studies of digital libraries.…”
Section: Digital Library Evaluation Framework/modelsmentioning
confidence: 99%